PENGARUH SISTEM AKUNTANSI PEMERINTAH DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH KOTA BENGKULU - Rina Yuniarti (UNIVED Press, 2015)
Rina Yuniarti; Based on Government Regulation No. 24 Year 2005 regarding the Government Accounting Standards (SAP). Government Accounting Standards are accounting principles applied in preparing and presenting the financial statements of the government. Thus, the Government Accounting Standards are requirements that have the force of law in an effort to improve the quality of financial reports of government agencies. good reporting system is needed in order to monitor and control the performance of managers in implementing budget diterapkan.Penelitian aims to determine the effect of government accounting systems and reporting on performance accountability system. The research sample SKPD in Bengkulu city government. Data analysis technique used is the regression berganda.Hasil this study indicate that the government accounting system affect the performance accountability and reporting systems and the effect on performance accountabilityKey words: Government Accounting System, System Reporting, PerformanceAccountability